Can an educational video improve the adequacy of bowel preparation for patients undergoing their first colonoscopy? Results of the EBOPS RCT - Archer, Thomas; Corfe, Bernard; Dear, Keith; Cole, Andy; Foley, Stephen; Andreyev, H Jervoise N; Fateen, Waleed; Baxter, Andrew; Riley, Stuart; The EBOPS study group; Parra-Blanco, Adolfo; Thoufeeq, Mo (Endoscopy International Open, 2024)
Background and study aims The aim of this study was to assess the effect of an educational video on the quality of bowel preparation of patients from a UK population attending for their first colonoscopy.Patients and methods A prospective, endoscopist-blinded trial with 1:1 allocation was performed. Patients referred for their first colonoscopy were recruited between February 2019 and December 2019. All participants were prescribed Moviprep and received the trial site’s standard written bowel preparation instructions, with the intervention group also receiving a bespoke educational video. Adequacy of bowel preparation (defined as a Boston Bowel Preparation Scale of ≥2 in each segment of the bowel) and polyp detection rates (PDRs) were compared. Fisher’s chi squared test was utilized with P <0.05 as the threshold for significance.Results A total of 509 participants completed the trial from six centers; 251 were randomized to the intervention group. The mean age was 57 years and 52.3% were female. The primary endpoint was met with an adequacy rate of 216 of 251 (86.1%) in the intervention group, compared with 205 of 259 (79.1%) in the control group (P <0.05, odds ratio [OR] 1.626, 95% CI 1.017–2.614). The PDR was significantly higher in the intervention group (39% vs 30%, OR 1.51, 95% CI 1.04–2.19, P <0.05).Conclusions An educational video leads to improved bowel preparation for patients attending for their first colonoscopy, and is also associated with greater detection of polyps. Widespread adoption of an educational video incurs minimal investment, but would reduce the number of inadequate procedures, missed pathology, and the cost that both these incur.